SELF‐PERCEIVED JOB INSECURITY AND THE DEMAND FOR MEDICAL REHABILITATION: DOES FEAR OF UNEMPLOYMENT REDUCE HEALTH CARE UTILIZATION?. (4th October 2013) - Reichert, Arndt R.; Augurzky, Boris; Tauchmann, Harald
ABSTRACT: An inverse relationship between job insecurity and sickness absence has been established in the literature, which is explained by employees avoiding to send signals of both poor health and uncooperative behavior towards the employer. In this paper, we focus on whether the same mechanism applies to the demand for medical rehabilitation measures. This question has recently gained much interest in the context of the current public debate on presenteeism. Using county‐level unemployment rates as instrument for the employees' fear of job loss on the individual level, we find that an increase in subjective job insecurity substantially decreases the probability of participating in medical rehabilitation. Copyright © 2013 John Wiley & Sons, Ltd.